Partnering for real world learning, sustainability, tourism education. Issue 4 (7th September 2015) - Barry O'Mahoney, Prof.; Jennings, Gayle; Cater, Carl I.; Hales, Rob; Kensbock, Sandra; Hornby, Glen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this article is to study how real world learning was used to engender and enhance sustainability principles and practices with 11 micro-, small- and medium-tourism business enterprises and 101 university tourism students enrolled across three university courses. Design/methodology/approach – Action research processes were used to focus curricula on "education about and for sustainability". A participatory paradigm informed the action research processes. The key methodology was qualitative. Empirical materials were generated through lived experiences, reflexive team conversations, team journals, reflexive journals and student learning materials. Reflexive conversations and reflective dialogue framed interpretations. Findings – The action research process found that pedagogies, andragogies and ethnogogies that emphasize social processes of meaning making and sensemaking enhance and engender "education about sustainability" and "education for sustainability", especially when coupled with real world learning as a platform for social and profession-building processes between university students, course teaching staff and industry, in this case, micro-, small- and medium-tourism entrepreneurs. Research limitations/implications – The qualitative findings of this action research study are specific to the participants involved. Generalizability to other university and business settings and goodness of fit require further study. Practical implications – Insights are provided with regard to implementing real world learning in university undergraduate and postgraduate courses by partnering with industry and focusing on education for sustainability (EfS). A demonstration of the effectiveness of action research as a tool for changing curricula is provided. Social implications – Learning is a social process of meaning making. Time for real world social interaction is critical for learning. Partnering with industry complements student learning and facilitates the translation of theory into practice. Originality/value – EfS is engendered and enhanced when learning-teaching engagements are predicated on real world settings, circumstances and experiences.